Audre Lorde, una memoria plástica para estallar la diferencia. - Barrientos, Panchiba F. (Nomadías, 2017)
What name should we give to those narratives that construct knowledge from the exposition of an experience that is both personal and deeply collective? In this text I want to re-read Audre Lorde in the light of the concept of plastic memories, which arises from a triple conjunction between the autobiographical writings set up by black and Chicano authors and poets of the 70s and 80s of the 20th century in the United States. Idea of plasticity developed by Catherine Malabou and the concept of figuration articulated by Rosi Braidotti. A plastic memory is capable of blowing the dominant mandates of gender, race and sexuality, highlighting their silences. A plastic memory is a reappropriaΩtion of the negated word, a trembling that crosses the fictional routes of our imaginary, in an attempt to value new ways of saying and thinking what happens beyond the limits of the great lanterns of history.